“Poetry as Social Criticism: A Comparitive Study of Poonthanam and Ayyappa Paniker” - Krishnan , Medha U; Shilpa P; C.S.Jayaraman (International Journal of Psychosocial Rehabilitation, 2020)
The paper is an attempt to examine the poetry of two Malayalam poets, Poonthanam, a 16th century Bhakthi poet, and Dr.K.Ayyappa Paniker, a seminal influence on modern Malayalam poetry. Though belonging to two different historical backgrounds and socio-cultural milieus, their poetry closely reflected contemporary life and prevalent social issues. Poonthanam’s poetry attempted to articulate sombre philosophical concepts in simple lyrical style, easily accessible to common people, whereas Ayyappa Paniker’s poems were subtle expose’s, bitingly sarcastic in style. Casteism and upper-class hegemony were the prominent social issues which Poonthanam’s poetry addressed, whereas in the poetry of Ayyappa Paniker, these are only a few among other complex social issues engendered by modern age. The paper is an attempt to tease out the social dimensions in the works of Poonthanam and Ayyappa Paniker, taking into account, at the same time, the affinities and divergences in their poetry. Poonthanam’s Jnanappana